SINAIS DISTINTIVOS: Dificuldades e perspectivas do registro de marcas coletivas e indicações geográficas para artesanato de tradição cultural. - SAMPAIO JUNIOR, Jeferson Oriente Brelaz (Universidade Federal do Oeste do Pará, 2024)
This study reflects the experience arising from work plans developed in the year 2011 and 2012 under the Cultural Heritage Outreach Program in the Amazon ( PEPCA ) , the Federal University of Western Pará ( UFOPA ) . At the time were held extension actions for dissemination of collective marks and geographical indications in market access strategies and legal advice for the registration of Collective Brand for cultural goods produced from ways of making cultural tradition and representative of the region the Para west, namely: craft ornate black bowls of Riparian Artisans Association of Santarém ( ASARISAN ) and twisted tucumã straw of the Association of Artisans of Arapiuns ( AARTA ) . The activities carried out primarily with the artisans of Aritapera , raised relevant analyzes , expressed in concerns and possibilities for the use of distinctive signs to identify cultural tradition of durable, practical result of popular groups . The present work starts from literature review on Intellectual Rights , Intellectual Property and Cultural Heritage , and by reviewing reports produced from the research and extension activities , aims to study the use and registration of these institutes for goods cultural traditions , such as handicrafts made by local communities from traditional knowledge and ways of doing recognized as intangible cultural heritage , analyzing the difficulties and prospects posed by the Intellectual Property System .